Translator's Visibility: An assessment study of Al- Kharbutli's translation of Irving's Life of Mahomet - Hashem, Fatima (An Najah National University, 2024)
Abstract This study aims to investigate Ali Husni Al-Kharbutli's translation of Washington Irving's Life of Mahomet (1850) in light of Venuti's (1995) approach of Visibility and Invisibility of the translator, in addition to the relevant strategies of Domestication and Foreignization. An examination is carried out to check whether the translator performed mediation or intervention, considering the extent to which he employed or mitigated ideologically saturated lexis and syntactic structures. The main source for data analysis in this thesis is a corpus of instances derived from the sourcebook Life of Mahomet (1850) and its well-received translation among Arab audienceحياة محمحمد (1966) by Ali Husni-Al Kharbutli. At the lexical level, the data is categorized into sections showcasing the salient stereotypes manifested through the author's lexical choices, which are symptomatic of his view pertinent to the Islamic faith and the character of the Prophet of Islam. These were compared with their translations to measure the degree of changes introduced by the translator. Whereas, at the syntactic level, examples are classified based on the most notable procedures employed by the translator, by reference to their bearing on the ST. The theoretical framework adopted in this thesis is Farghal's (1993) managing; which draws a distinction between intrinsic and extrinsic management on different textual levels, in the case of extrinsic management these levels are; lexical, syntactical, and discursive. . However, the present study tackles extrinsic management on the levels of lexis and syntax. Evidence revealed that blatant intervention resulted in the manipulation of the ST and misrepresentation of its spirit, due to the visibility of the translator's ideology particularly through the heavy implementation of omission. Such intervention alters the original sense of the ST, impeding the author's original perception from reaching out to the TR. Consequently, translators shall achieve an equilibrium between their urge to inject their voice and their primary mission of conveying that of the author, since the translator's role lies in their ability to communicate the author's view of a particular issue, not providing an alternative one, lest they fall in the trap of their own biases. Drawing upon that, a translator shall be extensively informed of translation constraints and norms, particularly when approaching texts with a sensitive nature, such as cultural and religious texts. To wrap up, the translator's intervention ranged from mild to drastic leading to a loss of meaning and excision of the author's ideology on several occasions, therefore, the translator should have considered reaching a consensus between fidelity to the ST and cultural sensitivity of the TT.
Positive Thinking, Tolerance, and Optimism Among Students at An-Najah National University in Nablus Governorat